2010
DOI: 10.12968/bjom.2010.18.5.47859
|View full text |Cite
|
Sign up to set email alerts
|

Women's worries about childbirth: making safe choices

Abstract: The aim of this research was to provide a qualitative account of a number of women's everyday worries about childbirth. This was facilitated by asking women about their worries and identifying their social and personal contexts. The central findings of this Australian study were that women worry about their own health and their baby's; normality and the effects of their pregnant and potential birthing behaviours. In addition the study showed that pain is linked with vulnerability and that women feel they are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 17 publications
1
22
0
1
Order By: Relevance
“…'Please indicate why you would prefer an epidural (for your partner)? ' 8 A review of the literature revealed more than 10 different self-report measures of childbirth fear (4,5,(20)(21)(22)(23)(24)(25)(26)(27)(28), ranging from 1-item measures (26,27,29) to a 64-item scale (5). The 33-item Wijma Delivery and Expectancy Questionnaire (WDEQ) (20) is the most commonly employed measure and has been used in several countries (1-3, 30-32).…”
Section: Sample 6 (Usa)mentioning
confidence: 99%
See 1 more Smart Citation
“…'Please indicate why you would prefer an epidural (for your partner)? ' 8 A review of the literature revealed more than 10 different self-report measures of childbirth fear (4,5,(20)(21)(22)(23)(24)(25)(26)(27)(28), ranging from 1-item measures (26,27,29) to a 64-item scale (5). The 33-item Wijma Delivery and Expectancy Questionnaire (WDEQ) (20) is the most commonly employed measure and has been used in several countries (1-3, 30-32).…”
Section: Sample 6 (Usa)mentioning
confidence: 99%
“…Severe fear of childbirth affects 2.5% of nulliparas and 4.5% of multiparas (6) and is characterized by nightmares, physical complaints, and difficulties concentrating on work or family activities. Common childbirth fears include worries about the health and safety of the baby, and fear of intolerable pain, prolonged labour, an inability to cope with labour and unsupportive hospital staff (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Women most commonly fear labour pain and harm to the baby (Geissbuehler andEberhard, 2002, Melender, 2002;Saisto and Halmesmaki, 2003;Maier, 2010;McAra Couper et al, 2010); they view their fears as mitigated by obstetric interventions, such as epidural anaesthesia for relief of labour pain and planned CS to avoid labour pain (Stoll & Hall, in press-a). Most studies of childbirth fear have focused on pregnant women and their partners, with little attention paid to fear of birth and preferences for obstetric interventions among the next generation of maternity care consumers (Saroli-Palumbo et al, 2012;Stoll and Hall, in press-a, in press-b).…”
Section: Introductionmentioning
confidence: 99%
“…Underpinning the biomedical approach is the view that pregnancy and childbirth are inherently risky, and therefore in need of medical supervision and technological interventions (Symon 2006). The laudable aim of risk management in maternity services is to improve the quality of care and patient safety (Heyman et al 2010), yet this approach has contributed to the ever increasing rates of medical intervention in pregnancy and birth (Maier 2010, Fenwick et al (2010. These practices are congruent with Beck's (1992) and Giddens' (1990) well-established thesis that risk and the management of risk has become increasingly important and pervasive in contemporary late-modernity.…”
Section: Introductionmentioning
confidence: 99%